Catalytic Conversion of 1‐butene over Modified Versions of Commercial ZSM‐5 to Produce Clean Fuels and Chemicals. Issue 16 (19th February 2019) - Silva, Andreia F.; Fernandes, Auguste; Antunes, Margarida M.; Ribeiro, Maria F.; Silva, Carlos M.; Valente, Anabela A.
Abstract: The oligomerisation of light olefins, obtainable from fossil/renewable sources and refinery streams, is an attractive route to produce clean synthetic fuels and added‐value chemicals. ZSM‐5 is a type of catalyst used in commercial olefin oligomerisation processes. Using appropriate modification procedures, it was possible to prepare catalysts with improved performances. Various modified versions of commercially available ZSM‐5 were prepared and investigated for 1‐butene oligomerisation under high‐pressure, continuous‐flow operation (30 bar, 200 °C). Simple, up‐scalable top‐down strategies involving base‐acid treatments of ZSM‐5 led to catalysts possessing enlarged pores and the required acidity for converting 1‐butene to higher molar mass products. In targeting diesel type products, the modified catalysts led to up to 86 % butenes conversion, space time yield of 852 mg gcat −1 h −1 and mass ratio diesel:naphtha cuts of 2.2. Characterisation studies and multivariate/principal component analysis helped categorise the differently prepared catalysts, and gain insights into complex interplay of material properties influencing the catalytic reaction. Abstract : A clean start : ZSM‐5 is a type of catalyst used in commercial olefin oligomerisation processes to produce clean synthetic fuels. Using appropriate top‐down procedures, it was possible to modify the material properties to improve the catalytic performance for 1‐butene oligomerisation. Superior performances may be met for an intermediate amount of acid sites and prevailing mesoporosity.